Pengaruh Pengetahuan Anggota DPRD Tentang Anggaran Terhadap Efektifitas Pengawasan Anggaran (Studi Empiris Pada Kabupaten Kampar) - Aras Aira (Kutubkhanah, 2012)
The research soughtly to test the effect of knowledge of the budget on the budget supervision effectivity. Dependent variables in this research is knowledge of the budget, Independent variable is the budget supervision effectivity. The population of the research was the members of parliament serving for the period of 2009- 2014. The data were the collected using a quaestionnaire to 43 members of parliament, however only 34 quaestionnaires were returned. The result revealed that the knowledge of the budget had sufficient effect on the budget supervision effectivity.